Effectiveness of acupuncture treatment for stroke and stroke complications: a protocol for meta-analysis and systematic review based on randomized, single-blind, controlled trials - Wang, Xiao-Yu; Liu, Wei; Li, Huan; Rong, Meng-Ying; Li, Jing-Yu; Wang, Shao-Kang; Du, Yu-Zheng; Zhao, Qi (Frontiers in Neurology, 2023)
The treatment and rehabilitation of stroke and its complications have become a major global health issue. Acupuncture is widely used as a complementary and alternative treatment for stroke. Currently, many clinical studies have evaluated the efficacy and safety of acupuncture, but the research results need to be more consistent. The quality of research based on previously published meta-analyses is uneven, leading to unstable conclusions. This study aimed to provide a comprehensive and systematic analysis on the efficacy of high-quality randomized controlled trials based on blinded designs for treating stroke and its complications. It also aimed to review the characteristics of blinded designs and the current use of sham/placebo acupuncture controls in treating stroke.Methods and analysis: This study will be conducted under the reporting guidelines for systematic reviews and meta-analyses. Randomized controlled trials using acupuncture as the primary measure for stroke were searched in databases such as China National Knowledge Infrastructure (CNKI), Chongqing VIP (CQVIP), Wan-fang, PubMed, Embase, Cochrane Library, and Web of Science. To evaluate high-quality research based on blind design, if the trial evaluates the efficacy of any acupuncture intervention by including a sham/placebo acupuncture control, it will be included. The primary outcome was the ability to perform daily living. Secondary outcome indicators include evaluating quality of life and related functions in stroke-related sequelae. We will assess the quality of evidence, reporting quality and risk of bias for the acupuncture intervention in the literature included in this study using the GRADE system, the STRICTA 2010 checklist, and ROB2.0 respectively. RevMan 5.4 software will be used to conduct the meta-analysis, and Stata 15.0 software will be used for sensitivity analysis and publication bias testing.Discussion: By analyzing high quality well-designed, randomized controlled trials of acupuncture, this study's results may contribute to a more objective and standardized evaluation of acupuncture efficacy in treating stroke and its complications.